Predictor of hip fracture type: a systematic review - Matrangolo, Maria Rosaria; Smimmo, Alessandro; Vitiello, Raffaele; De Fazio, Andrea; El Motassime, Alessandro; Noia, Giovanni; Minutillo, Felice; Maccauro, Giulio (Acta Biomedica Atenei Parmensis, 2023)
BACKGROUND & AIMIn literature, many risk factors have been related to proximal femur fracture, but most of the studies do not explore differences between femoral neck fractures (FNF) and pertrochanteric fractures (PF). The aim of the paper is to review the current literature n order to assess risk factors associated with a specific pattern of proximal femur fracture. METHODSNineteen studies met the inclusion criteria and were taken into consideration in the review. Data reported from the included articles were age, gender of the patient, type of femoral fracture, BMI, height, weight, soft tissue composition, BMD, vitamin D levels, PTH levels, hip morphology and hip osteoarthritis. RESULTSBone mineral density (BMD) of the intertochanteric region result significant lower in PF, while BMD in femoral neck regione was lower in FNF. Low levels of Vit D with high PTH are observed in TF whereas low levels of vit D and normal PTH in FNF. Hip osteoarthritis (HOA) is significant less present and less severe in FNF, while in PF is usually more frequent or higher grade. CONCLUSIONSPatients with pertrochanteric fracture are older, with a low cortical thickness in the femoral isthmus, low BMD in the intertrochanteric region, severe HOA, low mean haemoglobin and albumin levels and hypovitaminosis D with a high PTH levels. Patients with FNF are younger, taller, with higher body fat mass, with lower BMD levels in femoral neck region, mild HOA, hypovitaminosis D without PTH response.